Methylation Profile of X-Chromosome–Related Genes in Male Breast Cancer - Foschini, Maria P.; Morandi, Luca; Sanchez, Alejandro M.; Santoro, Angela; Mulè, Antonino; Zannoni, Gian Franco; Varga, Zsuzsanna; Moskovszky, Linda; Cucchi, Maria C.; Moelans, Cathy B.; Giove, Gianluca; van Diest, Paul J.; et al. (Frontiers in Oncology, 2020)
Background: Androgen Receptor (AR) has been described to play a prominent role in Male Breast Cancer (MBC). It maps on chromosome X, and recent reports indicate that X chromosome polysomy is frequent in MBC. Since the response to anti-androgen therapy may depend on AR polysomy and on its overexpression similarly to prostate cancer, aim of the present study was to investigate the DNA methylation level of AR and its coregulators, especially those mapped on the X chromosome, that may influence the activity of AR in MBC. Methods: The DNA methylation level of AR, MAGEA2, MAGEA11, MAGEC1, MAGEC2, FLNA, HDAC6, and UXT, mapped on the X chromosome, was evaluated by quantitative Bisulfite-NGS. Bioinformatic analysis was performed in a GalaxyProject environment using BWA-METH, MethylDackel, and Methylation Plotter tools. The study population consisted of MBC (41 cases) compared with gynecomastia (15 cases). Results: MAGEA family members, especially MAGEA2, MAGEA11, MAGEC, and UXT and HDAC6 showed hypomethylation of several CpGs, reaching statistical significance by the Kruskal-Wallis test (p<0.01) in MBC when compared to gynecomastia. AR showed almost no methylation at all. Conclusions: Our study demonstrated for the first time that MAGEA family members mapped on X chromosome and coregulators of AR, are hypomethylated in male IDC. This may lead to their overexpression, enhancing AR activity, while AR itself shows very little methylation.